Analysis of the importance of nutrition in the performance of professional football athletes (Research, Society and Development, 2023)
Football is the most popular sport in the world, a practice that physically demands a lot from athletes due to its high level of intensity, number of games during the season, number of training sessions and little time for rest, requiring a specific strategy to align nutrition and the physical conditioning. In this way, the objective of this work was to analyze the importance of nutrition in the performance of the professional soccer player. The methodology used was a descriptive literary review with articles published from 2012 to 2023, research of articles was carried out in the databases of PUBMED (public/publisher), Google Scholar (Google Scholar) and Scielo (Scientific Electronic Library Online). Thus, it was observed that the consumption of nutrients such as carbohydrates (CHO), proteins (PTN) and lipids (LIP) aligned with hydration and, if necessary, supplementation, are fundamental for the positive results of the players and consequently for the club in general. This demonstrated the importance and need for the presence of a nutrition professional to achieve good results for the club and high performance for the players. It is concluded that from the presented data, it was verified that the soccer clubs need to introduce in the projects for the season of the team a Nutrition professional, acting in the performance of the players and in the prevention of injuries.